Watches bidding system application - Ng, Wei Bin (2022)

(untitled)
This report gives people a mobile application to conduct watch auctions online. It offers people the possibility of auctioning off as many models of watches as they like to view the app to find out any information about the product and bid for the goods' ownership. In this application, the bidder acts as a bidder, and the seller acts as a publisher. The publisher must provide the auction's duration, watches information and the product's initial price. After filling in the information, the system then takes the information given by the publisher, implants it into the auction for a certain period, and displays it to all users. The bidder can observe the watch with the 3D model in an augmented reality environment. To ensure the authenticity and security of the user and avoid people opening unauthorized accounts to bid, the application has a fingerprint biometric technical and 6-digit password verification method to ensure that the bidder is bidding with a realaccount. Each bidder can use the virtual currency called "MC coin" to bid on the items. The application uses the Google Firebase method to store all user and auction data. To stimulate sales and increase user trust in the product, the publisher is provided with the ability to upload a video and showcase the authenticity and comprehensive development. The user can have a conversation with the virtual customer service through the Chatbot function of this application, and the user can ask some basic or popular questions.